Incidence, recurrence, and prevalence of bacterial vaginosis from acute to chronic HIV infection in a prospective cohort of women in South Africa - Asare, Kwabena; Ngcapu, Sinaye; Osman, Farzana; Vandormael, Alain; Mindel, Adrian; Naicker, Nivashnee; Khanyile, Mlungisi; S. Abdool Karim, Salim; Tomita, Andrew; Garrett, Nigel (Annals of epidemiology, 2023)
Purpose - We investigated the incidence, recurrence, prevalence, and risk factors for bacterial vaginosis (BV) diagnosis starting from acute HIV infection among South African women. - Methods - The Centre for the AIDS Programme of Research in South Africa 002 study tested and treated women for BV (Nugent score 7-10) once/twice annually from acute to chronic HIV infection (2004-2020). We estimated BV incidence as the number of new cases and recurrence as the number of subsequent diagnoses per 100 person-years (PYs). We fitted Anderson-Gil Cox-proportional-hazard regression models to determine factors associated with BV incidence or recurrence. - Results - Of 235 participants, the median age at enrollment was 25 years (Inter Quartile Range [IQR] 22-29). BV prevalence at enrollment was 50.6%. BV incidence was 23.9 cases per 100 PYs, and recurrence was 51.3 cases per 100 PYs. BV incidence/recurrence was associated with younger age (<25 years: adjusted hazard ratio [aHR] 1.70, 95% confidence interval [CI] 1.27-2.27), detectable HIV viral load (aHR 1.54, 95% CI 1.27-1.87) and lower CD4 count (<350 cells/μL: aHR 1.33, 95% CI 1.01-1.76). - Conclusions - Our findings underscore the need for early antiretroviral treatment initiation with diagnostic BV and sexually transmitted infection care, especially among younger women.
Online verfügbar 8. April 2023, Artikelversion 5. Mai 2023
Gesehen am 21.07.2023